A new snake species of the genus Boaedon Duméril (Serpentes: Lamprophiidae) from the African Great Lakes region - (:unkn) unknown (My University, 2022)
A new snake species from the genus Boaedon is described from Kigali, Rwanda. This speciesis clearly distinct molecularly from Boaedon fuliginosus and Boaedon lineatus with whom it was previouslyconfused, as well as other species recently or anciently described in this complex of morphologicallyclose species. Its geographical distribution covers eastern Central Africa in Rwanda, Burundi and theDemocratic Republic of the Congo, as well as Uganda and Tanzania in East Africa.
Keywords: African Research